Freedom--writing in anger - Majumdar, Biplab K. (New Delhi : Ess Ess Publications, 1998)
The corrupt practices of Indian National Congress behind the partition of India in 1947.
Includes bibliographical references (p. [iii]-[iv] and index.
Keywords: Indian National Congress; Political corruption -- India; India -- History -- Partition, 1947.; India -- Politics and government -- 1919-1947.